Czech Republic : 2012 Article IV Consultation: Staff Report: Staff Supplements; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Czech Republic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Economic activity in the Czech Republic is expected to remain flat in 2012 and gradually gain momentum as external conditions improve. The 2012 Article IV Consultation discusses that monetary conditions have been appropriately supportive of economic activity. The Czech financial system has proved resilient to the effects of the global crisis. Directors have commended the significant progress made in consolidating public finances and the authorities' strong commitment to long-term fiscal sustainability. Directors have also discussed the appropriate fiscal policy stance in light of the weaker economic outlook for 2012.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet